2023
DOI: 10.1177/00472875231175083
|View full text |Cite
|
Sign up to set email alerts
|

“I Love It” Versus “I Recommend It”: The Impact of Implicit and Explicit Endorsement Styles on Electronic Word-of-Mouth Persuasiveness

Abstract: Consumers usually endorse tourism products differently when sharing positive electronic word-of-mouth (eWOM). This research examines the relative persuasiveness of two endorsement styles, that is, explicit endorsement (e.g., “I recommend it”) and implicit endorsement (e.g., “I love it”). Drawing on the persuasion knowledge model, we propose that explicit endorsements are less persuasive than implicit endorsements because the former trigger stronger persuasion knowledge. We further argue that source trustworthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…For instance, the extant research has shown that explicit endorsements tend to be more persuasive than implicit ones when information source is trustworthy (Packard and Berger, 2017). By contrast, implicit endorsements are more effective in persuasion than explicit ones when information source is unfamiliar to prospective consumers (Liao et al, 2023). Different from those studies, our study investigates the effects of implicit versus explicit language styles in the context of negative marketing information.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, the extant research has shown that explicit endorsements tend to be more persuasive than implicit ones when information source is trustworthy (Packard and Berger, 2017). By contrast, implicit endorsements are more effective in persuasion than explicit ones when information source is unfamiliar to prospective consumers (Liao et al, 2023). Different from those studies, our study investigates the effects of implicit versus explicit language styles in the context of negative marketing information.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, many studies rely on experimental designs to assess the influence of linguistic features in NORs (e.g. Liao et al, 2023;Packard and Berger, 2017). However, future research has the opportunity to leverage AI-assisted tools to complement experimental designs, providing a more comprehensive understanding of the effects of NORs with implicit and explicit conclusions.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Future research could take these factors into account and expand the proposed model. Mental time travel involves both explicit and implicit cognitive processes (Gawronski et al, 2020;Kihlstrom, 1990;Liao et al, 2023). Reliance on self-report methods is limited as they mainly identify explicit cognitions while ignoring implicit biases.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%